Stabilized complexes of epidermal growth factor and its receptor on the cell surface stimulate RNA synthesis but not mitogenesis. - Wakshull, E M (1985)
Treatment of mouse fibroblasts, prelabeled at 4 degrees C with 125I-labeled epidermal growth factor (EGF), with the lectin concanavalin A (Con A) stabilized the 125I-labeled EGF-receptor complex to dissociation and prevented receptor-mediated endocytosis; after 5 hr at 37 degrees C, approximately 50% of the 125I-labeled EGF initially bound at 4 degrees C remained cell associated, compared to less than 15% in control cells. The radioactivity lost from the Con A-treated cells was found as intact hormone in the medium, with almost no hormone degradation evident, whereas in control cells most of the medium radioactivity was in the form of low molecular weight degradation products. The trimolecular complex Con A-EGF-receptor was capable of stimulating RNA synthesis to levels greater than control (untreated) or EGF alone and maintained this stimulation for prolonged periods of time. However, there was no effect of Con A treatment on the stimulation of DNA synthesis induced by EGF prebound at 4 degrees C. Thus, maintaining the EGF-receptor complex at the cell surface allows enhanced stimulation of an acute biological response to EGF (RNA synthesis) but not stimulation of DNA synthesis. These data support the idea that processing subsequent to receptor binding is necessary to produce the mitogenic signal.